THE ROLE OF DATA SECURITY IN CUSTOMER RELATIONSHIP MANAGEMENT (CRM) SYSTEMS - Dinesh Rajasekharan, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution of Customer Relationship Management (CRM) systems has positioned them as critical repositories of sensitive customer data, making robust security measures essential. The integration of encryption, tokenization, and secure API protocols safeguards customer information while maintaining operational efficiency. Advanced security frameworks, including comprehensive logging, compliance automation, and multi-factor authentication, create resilient barriers against emerging threats. The convergence of artificial intelligence and machine learning with traditional security measures enhances threat detection and response capabilities. This systematic implementation of security controls, combined with proactive monitoring and adaptive technologies, enables organizations to protect valuable customer data while fostering trust and ensuring regulatory compliance in the digital age.